Arbuscular mycorrhizal fungi-mediated activation of plant defense responses in direct seeded rice (Oryza sativa L.) against root-knot nematode Meloidogyne graminicola - Malviya, Deepti; Singh, Prakash; Singh, Udai B.; Paul, Surinder; Kumar Bisen, Pradeep; Rai, Jai P.; Verma, Ram Lakhan; Fiyaz, R. Abdul; Kumar, A.; Kumari, Poonam; Dei, Sailabala; Ahmed, Mohd. Reyaz; et al. (Frontiers in Microbiology, 2023)
Rhizosphere is the battlefield of beneficial and harmful (so called phytopathogens) microorganisms. Moreover, these microbial communities are struggling for their exhistance in the soil and playing key roles in plant growth, mineralization, nutrient cycling and ecosystem functioning. In the last few decades, some consistent pattern have been detected so far that link soil community composition and functions with plant growth and development; however, it has not been studied in detail. AM fungi are model organisms, besides potential role in nutrient cycling; they modulate biochemical pathways directly or indirectly which lead to better plant growth under biotic and abiotic stress conditions. In the present investigations, we have elucidated the AM fungi-mediated activation of plant defense responses against Meloidogyne graminicola causing root-knot disease in direct seeded rice (Oryza sativa L.). The study describes the multifarious effects of Funneliformis mosseae, Rhizophagus fasciculatus and Rhizophagus intraradices inoculated individually or in combination under glasshouse conditions in rice plants. It was found that F. mosseae, R. fasciculatus and R. intraradices when applied individually or in combination modulated the biochemical and molecular mechanisms in the susceptible and resistant inbred lines of rice. AM inoculation significantly increased various plant growth attributes in plants with simultaneous decrese in the root-knot intensity. Among these, the combined application of F. mosseae, R. fasciculatus and R. intraradices was found to enhance the accumulation and activities of biomolecules and enzymes related to defence priming as well as antioxidation in the susceptible and resistant inbred lines of rice pre-challenged with M. graminicola. The application of F. mosseae, R. fasciculatus and R. intraradices, induced the key genes involved in plant defense and signalling and it has been demonstrated for the first time. Results of the present investigation advocated that the application of F. mosseae, R. fasciculatus and R. intraradices, particularly a combination of all three, not only helps in the control of nematodes but also increases plant growth as well as enhances gene expression in rice. Thus, it proves to be an excellent biocontrol and plant growth-promoting agent in rice even when the crop is under biotic stress of the root-knot nematode, M. graminicola.